Relanzamiento de la página web y creación de contenidos en redes sociales de M&J Construcción e Ingeniería - Guerra Zurita, María Antonella (2021)
The purpose of the project is to promote external communication on the digital platforms of the company M&J Construcción e Ingeniería, such as the corporate website and its social networks. These digital channels will be developed to give the company visibility in front of its corporate clients, which is its main target audience, and collaborators, which is its secondary audience, since it is a large group that interacts on social networks. This document presents the development of the web launch and the campaign, both on Facebook and LinkedIn, which support the image and positioning of the corporate website.